2021
DOI: 10.3389/fendo.2021.782118
|View full text |Cite|
|
Sign up to set email alerts
|

When to Start and Stop Bone-Protecting Medication for Preventing Glucocorticoid-Induced Osteoporosis

Abstract: Glucocorticoid-induced osteoporosis (GIOP) leads to fractures in up to 40% of patients with chronic glucocorticoid (GC) therapy when left untreated. GCs rapidly increase fracture risk, and thus many patients with anticipated chronic GC exposures should start anti-osteoporosis pharmacotherapy to prevent fractures. In addition to low awareness of the need for anti-osteoporosis therapy among clinicians treating patients with GCs, a major barrier to prevention of fractures from GIOP is a lack of clear guideline re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 87 publications
(174 reference statements)
0
10
1
Order By: Relevance
“…Chun-Yuan Chen et al collected EVs from human-urine-derived stem cells (USG), and then injected these EVs into a mouse model of osteoporosis, which proved that these EVs can enhance bone formation and inhibit osteoclast resorption; the specific mechanism is the enrichment of CTHRC1 and OPG proteins are necessary for inducing bone formation and inhibiting osteoclast resorption. Therefore, USC-EVs can be said to be a very promising method of treatment for osteoporosis [ 9 ]. Dawei Liu et al demonstrated that RNF146 in circulating apoptotic bodies can treat osteoporosis [ 21 ].…”
Section: The Potential Therapeutic Effects Of Evs In Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…Chun-Yuan Chen et al collected EVs from human-urine-derived stem cells (USG), and then injected these EVs into a mouse model of osteoporosis, which proved that these EVs can enhance bone formation and inhibit osteoclast resorption; the specific mechanism is the enrichment of CTHRC1 and OPG proteins are necessary for inducing bone formation and inhibiting osteoclast resorption. Therefore, USC-EVs can be said to be a very promising method of treatment for osteoporosis [ 9 ]. Dawei Liu et al demonstrated that RNF146 in circulating apoptotic bodies can treat osteoporosis [ 21 ].…”
Section: The Potential Therapeutic Effects Of Evs In Osteoporosismentioning
confidence: 99%
“…Although bisphosphonates have satisfactory therapeutic effects, they also have some side effects. Therefore, new prevention and treatment methods for osteoporosis are critical [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prevention and management of GIOP is addressed in several guidelines and has been extensively reviewed in other articles and is beyond the scope of this review (141)(142)(143)(144). It is worth highlighting that a dual-energy X-ray absorptiometry (DXA) scan for BMD measurement is required in the majority of cases for a fracture risk assessment.…”
Section: Bone Preserving Treatments In Vasculitis: the Role Of Steroi...mentioning
confidence: 99%
“…The etiology and pathogenesis of GIOP are not yet fully explicit, but most studies have found that the occurrence of this disease is significantly associated with an imbalance in bone remodeling [7,8] . When it is disrupted, bone formation is less than bone resorption, which leads to a decrease in bone strength and, ultimately to the onset of the disease.…”
Section: Introductionmentioning
confidence: 99%